2013
DOI: 10.4103/0970-9185.105809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeat exposure to inhalation anesthetics on liver and renal function

Abstract: Background:Cross hypersensitivity to inhalation anesthetics has not been studied. The aim of this study was to investigate it by comparing liver and renal function after repeated anesthesia with sevoflurane and isoflurane retrospectively.Materials and Methods:The adult patients who received general anesthesia twice within the interval of 14 days to 1 year were retrospectively analyzed. Those who received sevoflurane anesthesia twice (SS group, 53 cases), isoflurane anesthesia twice (II group, 31 cases), sevofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…As far as comparison between groups is concerned there was no statistically significant changes in AST, ALT, and ALKP for any of the anaesthetic agents under study, while statistically significant difference was observed for γGT between the VA and IA groups, while this increase was not higher than reference values. (Levine BS, 1995) In humans undergoing inhalation anaesthesia it has been observed that creatinine was within normal range, while BUN was affected in a small number of subjects with no clinical importance (Nishiyama, 2013) which is in agreement with our results. Male and female rats exposed to isoflurane anaesthesia through vaporiser presented decreased creatinine levels (Deckardt et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…As far as comparison between groups is concerned there was no statistically significant changes in AST, ALT, and ALKP for any of the anaesthetic agents under study, while statistically significant difference was observed for γGT between the VA and IA groups, while this increase was not higher than reference values. (Levine BS, 1995) In humans undergoing inhalation anaesthesia it has been observed that creatinine was within normal range, while BUN was affected in a small number of subjects with no clinical importance (Nishiyama, 2013) which is in agreement with our results. Male and female rats exposed to isoflurane anaesthesia through vaporiser presented decreased creatinine levels (Deckardt et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, some authors affirm that the transaminases' values were slightly increased after inhaled anesthesia with sevoflurane (Soubhia et al, 2011). Some of them write that isoflurane and sevoflurane anesthesia induces an increase in the seric concentration of hepatic enzymes, isoflurane inducing a greater increase in comparison to sevoflurane (Nishiyama, 2013), while others write that the seric level of aspartate-aminotranferase (ASAT) slightly increased in the first day after sevoflurane anesthesia (Sun et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Although these observations suggest impairment of proximal tubule function, these effects are consistently transient, and these findings do not indicate renal tubular injury, kidney tubule injury, per se (Kharasch et al 2001). Numerous reports indicate that these agents cause no detriment in glomerular filtration (Bito and Ikeda 1996;Bito et al 1997;Kharasch et al 1997Kharasch et al , 2001Ebert et al 1998;Higuchi et al 1998Higuchi et al , 2001Nishiyama et al 1998;Bito et al 1999;Goldberg et al 1999;Groudine et al 1999;Ebert and Arain 2000;Eger et al 1997a,b;Obata et al 2000;Conzen et al 2002;Nishiyama 2013), suggesting that they do not induce necrosis of tubule cells in humans. On the contrary, previous reports have shown that volatile anesthetics protect proximal tubule cells against ischemia (Zager et al 1999) and protect patients against ischemic nephropathy (Cai et al 2014;Fukazawa and Lee 2014).…”
Section: Discussionmentioning
confidence: 98%
“…2000; Conzen et al. 2002; Nishiyama 2013), suggesting that they do not induce necrosis of tubule cells in humans. On the contrary, previous reports have shown that volatile anesthetics protect proximal tubule cells against ischemia (Zager et al.…”
Section: Discussionmentioning
confidence: 99%